Association between hypothyroidism and chronic kidney disease observed among an adult population 55 years and older. Issue 17 (April 2020) - Huang, Cheng-Wei; Li, Bonnie H.; Reynolds, Kristi; Jacobsen, Steven J.; Rhee, Connie M.; Sim, John J.
Abstract : Abstract: Hypothyroidism and chronic kidney disease (CKD) are highly prevalent conditions with a potential mechanistic link. We sought to determine whether hypothyroidism is associated with CKD among a large diverse community-based cohort. A cross-sectional study was performed (January 1, 1990–December 31, 2017) within a large integrated health system. Individuals age ≥55 years of age with outpatient measurements of thyroid stimulating hormone (TSH) and ≥2 serum creatinine values were included. Hypothyroidism was defined as TSH >4 mIU/L and/or receipt of thyroid hormone replacement and further categorized as hypothyroid status: TSH >4 mcIU/mL and attenuated-hypothyroid status: TSH <4 mcIU/mL with receipt of thyroid hormone replacement. Euthyroidism was defined as TSH <4 mIU/L and no thyroid hormone replacement. Our primary measure was CKD defined as an estimated glomerular filtration rate (eGFR) <45 mL/min/1.73 m 2 . Multivariable logistic regression adjusting for age, sex, race, and comorbidities was used to estimate odds ratios (OR) for CKD by thyroid status. Among 378, 101 individuals, 114, 872 (30.4%) had hypothyroidism among whom 31, 242 and 83, 630 had hypothyroid and attenuated-hypothyroid statuses, respectively. Individuals with hypothyroidism had a CKD OR (95%CI) of 1.25 (1.21–1.29) compared with those with euthyroidism. Granular examination of thyroid statuses showed that hypothyroid and attenuated-hypothyroid statuses had CKD ORs (95% CI) of 1.59 (1.52–1.66) and 1.12 (1.08–1.16), respectively. A similar relationship was observed in analyses that defined CKD as an eGFR <60 L/min/1.73 m 2 . Among individuals 55 years and older, we observed that those with hypothyroidism were more likely to have CKD. A stronger association was found among patients of hypothyroid status compared with attenuated-hypothyroid status suggesting a dose dependent relationship.